Are we managing the risk of sharing Cyber Situational Awareness? A UK Public Sector Case Study - Davies, M; Patel, M (Institute of Electrical and Electronics Engineers, 2016)
The development of effective cyber situational awareness, that makes a significant contribution to the decision making process around information risk management, is an important goal for organizations across all sectors. The sharing of such information between and within organizations is seen as a key security enabler. This paper considers a case study of a UK Public Sector organization. The aim is to establish if the decision to share cyber situational awareness has been taken from an information risk management perspective, and to examine whether or not the organization is suitably well-placed, to manage the consequences of information loss, occurring as a result of the sharing process.